2018
DOI: 10.1016/j.ygyno.2018.08.014
|View full text |Cite
|
Sign up to set email alerts
|

Continuous improvement in primary Debulking surgery for advanced ovarian cancer: Do increased complete gross resection rates independently lead to increased progression-free and overall survival?

Abstract: Despite higher-stage disease and greater tumor burden, CGR rates, PFS and OS for patients who underwent PDS increased over a 13-year period. Surgical paradigm shifts implemented specifically to achieve more complete surgical cytoreduction are likely the reason for these improvements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
38
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(47 citation statements)
references
References 30 publications
8
38
0
Order By: Relevance
“…We concluded that this atypical learning curve could be attributed to the fact that a significantly greater number of splenectomy with distal pancreatectomy operations were performed in the latter period in the high-score group (from the 105th to the 208th case) resulting in an increase in the number of cases showing Clavien-Dindo IIIa complications (pancreatic fistula). This result concurs with that of previous studies in which the incidence of perioperative complications was shown to be associated with the degree of complexity of the surgical procedure [4], although Clavien-Dindo IIIa complications (which can be controlled and treated) were less likely to affect overall outcomes [37].…”
Section: Discussionsupporting
confidence: 91%
“…We concluded that this atypical learning curve could be attributed to the fact that a significantly greater number of splenectomy with distal pancreatectomy operations were performed in the latter period in the high-score group (from the 105th to the 208th case) resulting in an increase in the number of cases showing Clavien-Dindo IIIa complications (pancreatic fistula). This result concurs with that of previous studies in which the incidence of perioperative complications was shown to be associated with the degree of complexity of the surgical procedure [4], although Clavien-Dindo IIIa complications (which can be controlled and treated) were less likely to affect overall outcomes [37].…”
Section: Discussionsupporting
confidence: 91%
“…Interestingly, centralization and complete cytoreduction were identified as significant independent factors for 5-year DFS in the multivariable regression analysis, with an HR of 0.78 after centralization and HR of 0.76 the first 500 days and 0.43 after 500 days at complete cytoreduction. The MSKCC study reported an increased 5-year PFS, showing a PFS of 15%, 16% and 20% over time, which is similar to the 5-year DFS observed in the complete cohort in our study, 13% to 23%, over time, and for those treated with PDS + chemo, 15% to 26% [19]. For those who had complete cytoreduction at PDS, the 5-year DFS observed in this study was 28% before centralization and as high as 45% after centralization.…”
Section: Discussionsupporting
confidence: 87%
“…A Japanese single center study by Tate et al compared the 5-year OS in a hospital that went from low volume surgery to high volume surgery and showed an increased OS from 38.0% to 55.5%, respectively, numbers comparable to ours at complete cytoreduction [18]. An American single center study from Memorial Sloan Kettering Cancer Center (MSKCC), assessing advanced ovarian cancer patients for whom PDS had been performed, also showed an increased 5-year OS from 40% to 44% to 56% during [2001][2002][2003][2004][2005][2006][2007][2008][2009] and 2010-2013, respectively, as advanced surgery was introduced at MSKCC during this period [19]. Interestingly, their results are also similar to our results for women with complete cytoreduction at PDS comparing before and after centralized primary care.…”
Section: Discussionmentioning
confidence: 99%
“…The literature regarding degree of cytoreduction, rates of bowel resection, and ostomy formation/reversal at the time of surgery for advanced-stage ovarian cancer remains heterogenous and our findings may not be generalizable to all clinical settings. However, rates of optimal cytoreduction are similar to those reported in other institutional studies 32. The current report provides an initial examination into the outcomes after bowel surgery and ostomy formation among patients undergoing cytoreductive surgery.…”
Section: Discussionsupporting
confidence: 81%